Investigation of ozone decay half-life in dependence of temperature and humidity as well as H₂S and NH₃ oxidation mechanism - Taran, V.S.; Krasnyj, V.V.; Lozina, A.S.; Chechelnitskyi, O.G.; Schebetun, A.V. (Вопросы атомной науки и техники, 2017)
In the present research, a measurement method of ozone decay half-life τ (h) in air depending on the temperature and humidity is proposed. This method allows simulating the conditions of ozone generation during sanitizing of various premises. The ozone generation was carried out in a closed volume of 0.125 m³ by ozonator based on dielectric barrier discharge. Through measurement ozone decay at temperatures of 10, 24 and 40 °C and humidity φ ~ 10, 50, 80 % was calculated. The ozone decay was found to change depending on temperature and humidity. The productivity of ARAO-1 type generator has been determined at various conditions. The H₂S and NH₃ oxidation mechanism has been studied. It was revealed that 8.6 mg of O₃ is required for of 1 mg of H₂S oxidized and 1.8 mg of ozone is required for 1 mg NH₃ oxidation. Предложен метод измерения полураспада озона τ (ч) в воздухе в зависимости от температуры и влажности. Метод позволяет моделировать условия генерации озона во время санитарной обработки различных помещений. Генерирование озона проводилось в замкнутом объёме 0,125 м³ с помощью озонатора на основе диэлектрического барьерного разряда. Измерения полураспада озона проводились при температурах 10, 24 и 40 °С и влажности φ ~ 10, 50, 80 %. Установлена зависимость периода полураспада озона от температуры и влажности. Определена производительность генератора озона AРАО-1 при различных условиях. Изучен механизм окисления соединений H₂S и NH₃. Было установлено, что 8,6 мг О₃ требуется для окисления 1 мг H₂S и 1,8 мг озона требуется для окисления 1 мг NH₃. Запропоновано метод вимірювання напіврозпаду озону τ (год) в повітрі в залежності від температури і вологості. Метод дозволяє моделювати умови генерації озону під час санітарної обробки різних приміщень. Генерування озону проводилося в замкнутому просторі 0,125 м³ за допомогою озонатора на основі діелектричного бар'єрного розряду. Вимірювання напіврозпаду озону проводилося при температурах 10, 24 і 40 °С і вологості φ ~ 10, 50, 80 %. Встановлено залежність періоду напіврозпаду озону від температури і вологості. Визначено продуктивність генератора озону AРАО-1 при різних умовах. Вивчено механізм окислення сполук H₂S і NH₃. Було встановлено, що 8,6 мг О₃ потрібно для окислення 1 мг H₂S і 1,8 мг озону потрібно для окислення 1 мг NH₃.